Pendapatan dan Nilai Tambah Pengolahan Primer Kopi Arabika di Desa Sait Buttu Saribu, Kecamatan Pamatang Sidamanik, Kabupaten Simalungun - Jef Rudiantho Saragih (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2019)
Primary processing is the most important aspect in enhancing the added value at farm business level, but some farmers have not done yet. This study aims to analyze the income of arabica coffee farm business, the difference in farmers’ income that sells coffee in parchment and cherry red, and  the added value of selling in parchment. Data were analyzed with Revenue Cost Ratio (RCR), Independent Sample t Test, and added value analysis method of Hayami et al. (1987). The results showed that arabica coffee farming with parchment had a higher RCR and was significantly different from cherry red, and which sold both parchment and cherry red. Income of farmers who sell parchment is differs significantly from who sell cherry red and those who sell both parchment and cherry red.  The added value of primary processing is 30%, while the income of family labor from the primary processing is 69%.